When Integrative Law Meets Performance System: The Role of Education on Poverty Alleviation in Indonesia - Sinaga, Elvrida N. (Scientium Law Review (SLR), 2023)
The target of the Government of Indonesia to eradicate poverty by 2024 (faster than the 2030 Agenda of all members of the United Nations), faces formidable challenges. The challenges include that the Indonesian economy is quite vulnerable to shocks such as a pandemic, an increase in the number of poor people, and the expansion of the definition of poverty in Indonesia according to the World Bank has the potential to increase the number of poor people from 26.36 million people to 44 million people. Based on the normative method using integrative legal theory, this study yields two conclusions. Firstly, the critical role of education in addressing poverty is based on educational law as a means of bureaucratic and societal renewal, which is briefly presented in the existing SWOT matrix. Secondly, educational law dealing with extreme poverty is based on bureaucratic engineering through the norm and behavioral systems, while societal engineering is based on value systems. It is recommended to renew regulations on the performance of educational organizations based on poverty alleviation, and to promote values such as excellent bureaucratic services, active community participation in and around schools and universities, the autonomy and independence of school committees in reducing the financial burden of extreme poverty groups, the improvement of income for extreme poverty groups, and the reduction of poverty pockets, based on the SWOT matrix that is expected to become the Key Performance Indicator for educational departments, schools, and school committees.